Information Quality and Decision-making Effectiveness: A Study of Banks in Palestine - Abumandil, Mohanad S.S.; Hassan, Shahizan (International Review of Management and Marketing, 2016)
Studies carried out on large banking firms across the globe suggest that information quality affects decision making, and managers are likely to be blamed the most for making right or poor decisions. However, few of the previous studies focused on how information quality affects decision making among bank managers operating in Palestine, which revealed the important role of information quality in decision-making effectiveness. A sample of 146 bank managers in Palestinian banks was recruited. The data collected were analyzed by SPSS and PLS_SEM for descriptive and hypothesis testing. The findings indicated the relevance and importance of information quality dimensions to decision-making effectiveness in the banking sector of Palestine. The results can guide banks in Palestine to understand better and utilize the information facilities at their disposal towards the provision of sustainable banking services in Palestine. Keywords: Banking sector; Decision-making effectiveness; Information quality; JEL Classification: D7